Between Scholar and Jurist: The Controversy over the Research of Jewish Law Using Comparative Methods at the Early Time of the Field - Radzyner, Amihai (Journal of law and religion, 2007)
The "[Torah] scholar" and the "scientist" thus part waysThe Torah scholar and the Jurist both supplement each other's workAt the beginning of the 1950s (or thereabouts) Rabbi Yitzhak (Isaac) ha-Levi Herzog, Ashkenazi Rabbi of the State of Israel and a researcher of Jewish law, delivered a lecture to a group of lawyers. He opened with the following comments:Before beginning my lecture, I would like to correct an error in its title, and I would ask that the correction also be published in the press. The subject I chose to lecture on was "Knowledge and Will in Contract and Property in Mishpat ha-Torah." The words "In comparison with English law" were added subsequently, without my knowledge. In my introduction to the second volume of my English work on Mishpat ha-Torah, I have already condemned a conspicuous proclivity in large portions of the modern literature on Mishpat ‘Ivri, to invariably search for comparisons and analogies from external sources. In essence, from an internal, spiritual perspective, such a comparison—God forbid—is inconceivable, for as the heavens are higher than the earth, so the Divine Torah granted from heaven is higher than any kind of jurisprudential system produced by human intellect and spirit. At the most, it is useful for explanatory purposes, enlisting human intellect to invoke external concepts in explaining certain concepts of Mishpat ha-Torah for those who are not conversant with classical Jewish sources, but are familiar with other legal systems. Therefore, my lecture is not devoted to comparison but rather to explanation, in other words explaining with the assistance of concepts and definitions taken from English law.